Kepala Sekolah Yang Bermutu - Sudirman Tamin (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2020)
The headmater is the top administrator, the highest leader in the school. High quality schools are very much determined by the educational leadership carried out by the school principal. The principal must develop a new program as an innovation in managing the learning process in schools. He must guide all school officials, so that the learning process is of high quality which ultimately leads to graduates who are also of high quality. If the principal has displayed excellent leadership, the school will become a quality school and will be a struggle for the whole community. The principal must master modern education management. The school community has high hopes for the principal to advance a quality / high quality learning process. The quality of education is very dependent on input, process and ends with output. These three components play a very important role. The head of the school must make every effort to improve the quality of these three components, so that the quality of education always increases from year to year.Keywords : Headmaster, Learning Process, and Quality Graduates.